2012
DOI: 10.1111/j.1754-9485.2012.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of the Greulich–Pyle method in bone age determination among Australian children

Abstract: Our results show that the standards of G&P are an accurate means of BA determination in Australian children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 10 publications
0
22
1
2
Order By: Relevance
“…Researchers in different countries showed that skeletal ages determined using the Greulich and Pyle method were lower than the chronological ages for a large proportion of the sample both in males and females, and that the method underestimates chronological age ( 5 , 6 , 16 , 17 ). Although the difference is not significant, a study in Australia reported overall underestimation of skeletal age by 2.2 months: 1.5 months for females and 3.7 months for males ( 18 ).…”
Section: Discussionmentioning
confidence: 86%
“…Researchers in different countries showed that skeletal ages determined using the Greulich and Pyle method were lower than the chronological ages for a large proportion of the sample both in males and females, and that the method underestimates chronological age ( 5 , 6 , 16 , 17 ). Although the difference is not significant, a study in Australia reported overall underestimation of skeletal age by 2.2 months: 1.5 months for females and 3.7 months for males ( 18 ).…”
Section: Discussionmentioning
confidence: 86%
“…Height and BMI were expressed as SDS for chronological age and were calculated according to CDC growth data ( 17 ). Greulich-Pyle method was used for bone age determination and Bayley-Pinneau method for prediction of adult height ( 18 , 19 ). Marshall-Tanner method was used for sexual maturation staging ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Adult HtSDS, predicted adult height (PAHSDS) at baseline and PAH at latest available time after the start of treatment were calculated using the British 1990 population as the reference measurement10. Bone ages were reported by the radiologists at each centre caring for the patients, based on the Greulich-Pyle standard11. Predicted adult height at the start of treatment, and at the oldest available age, was calculated for children 6 years of age or older, who had follow-up bone ages reported 12 months or more after the start of treatment.…”
Section: Methodsmentioning
confidence: 99%